Investigating the connection between the global meteoric water line and the local meteoric water line within the Gauteng and North West provinces in South Africa - Manny Mathuthu; Naomi D. Mokhine; Segomotso Lee-Ann Bowker; Joseph Mathuthu; Johan Hendriks; Ingrid Dennis (Journal of Hydrology: Regional Studies)
Study Region: this study was conducted in the Gauteng and North West Provinces of South Africa, where ground water is the main source of high quality and clean water. Study Focus: The aim of this study was to characterize the recharge-discharge processes and identify the connection between the global meteoric water lines and the local meteoric water lines within the area of interest. About thirty-one (31) water samples were collected from these two provinces and stable isotopes of hydrogen (2 H, i.e., deuterium), and oxygen-18 (18 O) analyzed, utilizing the Picarro L2130-i Isotope H2O, Picarro Inc. New Hydrological Insights for the Region: Results show that, the Local Meteoric Water Line for Gauteng and North-West Provinces was δ2 H = 5.411 x δ18 O – 0.693 and δ2 H = 5.089 x δ18 O – 1.825, respectively. The D-excess, for both, is lower than that of the Global Meteoric Water Line, indicating the semi-arid nature of these provinces, which discharge via evapotranspiration. Water from the two sets of boreholes reflected a mixture of water influenced by evaporation during or before infiltration and water that infiltrated through fast preferential pathways of the dolomite fractures. Also, the average slope of the two provinces was 5.0885, indicating evaporation as a major process. The findings of this research contribute to understanding recharge and discharge mechanisms over the different aquifers in the study area.